Investigating the Validity of Soft Tissue Signs on Lateral Ankle X-Ray to Aid Diagnosis of Achilles Tendon Rupture in the Emergency Department - Owen Bodger (International Journal of Foot and Ankle, 2019)
AimsTo investigate the diagnostic validity of four radiological soft tissue signs Kager's sign (K), disruption to the tendon (D), loss of parallelism (P) and fusiform swelling of the tendon (F) on a lateral ankle x-ray to aid Achilles tendon rupture diagnosis.MethodsWe retrospectively identified two groups of patients; Group A consisted of patients with an Achilles tendon rupture and Group B included patients with a clinically intact Achilles tendon but with a lateral ankle ligament sprain. Three clinicians independently reviewed all patients' x-rays for each of the radiological features under investigation to determine whether a rupture was present or not. Inter-rater and Intra-rater reliability were calculated using the Kappa coefficient (Kc.) To determine the predicted value of the signs sensitivity, specificity, positive predicted values and negative predicted values were calculated.Results85 patients x-rays were included in this study; Group A n = 47, Group B n = 38. The most valid radiological sign appeared to be loss of parallelism (sensitivity 70%, specificity 97%, kappa 0.55-0.58).ConclusionClinicians reviewing a lateral ankle x-ray of a patient with an acute ankle injury should review the x-ray for loss of parallelism between the tendon and skin; identification of this radiological sign may alert the clinician to the possible diagnosis of a ruptured Achilles tendon. Reviewing this may reduce the number of missed Achilles ruptures.